Relationship between Learning Motivation and Reflection in Undergraduate Students - Tikhomirova T. S.; Kochetkov N.V (Moscow State University of Psychology and Education, 2019)
This article aims to study the relationship between personal reflection and the intensity of motivation for learning in a university.In order to achieve this goal, the following techniques were employed: A.V.Karpov and V.V.Ponomaryova's technique for identifying the individual level of reflectivity, and T.I.Ilyina's technique for assessing learning motivation in university students.The empirical study involved 143 subjects.The obtained data indicate that for the first-year students the meaning of the 'mastering the profession' motive is directly connected with their reflections on the present and future activities, while the meaning of the 'getting a diploma' motive is inversely correlated with the reflection of communication.In the second year, the intensity of the 'gaining knowledge' motive correlates with the reflection of communication, and the meaning of the 'mastering the profession' motive has an inverse relationship with the reflection of future activity.In the third year, the values of the motive for acquiring knowledge correlate with the integral indicator of reflection, whereas in the fourth year none of the reflection components are interconnected with the components of the motivation for learning in the university.